Holding personal information in a disease-specific register: the perspectives of people with multiple sclerosis and professionals on consent and access. Issue 2 (30th January 2009) - Baird, W; Jackson, R; Ford, H; Evangelou, N; Busby, M; Bull, P; Zajicek, J
Abstract : Objective: To determine the views of people with multiple sclerosis (MS) and professionals in relation to confidentiality, consent and access to data within a proposed MS register in the UK. Design: Qualitative study using focus groups (10) and interviews (13). Setting: England and Northern Ireland. Participants: 68 people with MS, neurologists, MS nurses, health services management professionals, researchers, representatives from pharmaceutical companies and social care professionals. Results: People with MS expressed open and altruistic views towards the use of their personal information to facilitate service provision and research, placing trust in responsible guardianship and legitimate use of their information. Participant's proposed that people with MS should be able to select their individual level of involvement in a register using levels of consent. It was agreed that access to the register should be governed by a guardianship committee composed of a range of stakeholders. People with MS did not wish their details to be used by marketing agencies and did not consider this a legitimate use of their data. Whilst participants were positive of the role a register could play in promoting research, participants felt that access to data by pharmaceutical industries should be administered by the guardianship committee. People with MS are concerned should their employers be able to access their personal information. Professionals were more cautious than people with MS in their approach to the use of patient personal data within a register. Conclusions: Whilst all stakeholders were positive of the benefits of an MS register, development of such a resource must incorporate robust data security and guardianship measures in order to ensure that, whilst opportunities are maximised, risks to the privacy of individuals and legal challenges to professionals are avoided.